Principles of water quality control - Tebbutt, T. H. Y. (Pergamon Press, 1992)
The definitive student text in its field for 25 years, this new edition takes an environmental perspective that is highly relevant in the context of current public policy debates. New material also includes EU regulations and changes in the UK water industry since privatisation. The latest technological developments are also taken into account.